Vein of Galen aneurysmal malformations associated with high output cardiac failure: Report of three autopsy cases - Malhotra, Reenu K.; Florez, Luisa; White, Dollett; Papasozomenos, Sozos; Covinsky, Michael; Bhattacharjee, Meena; Wang, Min (Journal of Pediatric Neurology, 2011)
Vein of Galen aneurysmal malformations (VGAMs) are rare congenital vascular, malformation. The malformation usually develops between the 6th to 11th wk of gestation. We report three autopsy cases, all prenatally diagnosed by ultrasound or fetal magnetic resonance imaging with VGAM with associated high-output cardiac failure. Prenatal fetal echocardiogram on two patients showed cardiomegaly, ventricular dilatation, pulmonary hypertension and reversed aortic flow. The cause of death in all the three patients was high-output cardiac failure due to VGAM. The autopsy findings confirmed feeding arteries from posterior cerebral arteries to VGAM in all patients. Other significant neuropathologic findings at autopsy were severe hydrocephalus, polymicrogyria, germinal matrix hemorrhage, periventricular leukomalacia, and microcalcification. The findings support that VGAM may be due to abnormal arterial venous communication and the most common cause of death in these patients is high-output cardiac failure. The presence of other associated brain abnormalities indicates a poor prognosis.
Keywords: Vein of Galen; aneurysm; malformation; cardiac failure; diagnosis; autopsy